Serum paraoxonase activity in patients with rheumatoid arthritis, its relationship with the clinical course and cardiovascular compications - S. V. Shevchuk; Y. S. Seheda; O. Y. Galyutina; N. P. Masik; O. V. Shevchuk (Regulatory Mechanisms in Biosystems, 2018)
Nowadays low paraoxonase activity is generally recognized as an independent risk factor of cardiovascular diseases involved in pathologic remodeling of the heart and vessels as well as thrombosis in the general population. But the role of paraoxonase activity in RA patients is unknown. Based on the above, the aim of the work was to study serum paraoxonase activity in patients with rheumatoid arthritis, to evaluate its association with clinical course and structural and functional status of the cardiovascular system. 67 patients with RA, 18 males and 49 females were studied. The control group consisted of 25 apparently healthy individuals. Rheumatoid arthritis was diagnosed according to international classification criteria ACR 2012. The indices of total cholesterol (TC), high density lipoprotein cholesterol (HDLC) and triglycerides (TG) in blood serum were determined by standard conventional methods. Low density lipoprotein cholesterol (LDLC) values were calculated by Friedwald formula. Serum paraoxonase activity was measured by spectrophotometric method. High resolution ultrasound and Doppler ultrasonography of the brachial artery were performed to study endothelium function. Sonographic B-mode scanning and pulsed Doppler ultrasound of heart and blood flow spectra were done on ultrasound scanner. Serum paraoxonase activity was found to be about 18.8% lower in the patients with RA than in the control group. Serum paraoxonase activity was shown to decrease proportionally to the increase of the age in RA patients. In the group of patients over 45, the level of the enzyme was 13.0% lower than in the patients over 30. The study established that the increase of systolic and diastolic arterial pressure is associated with decrease of serum paraoxonase activity in RA patients. The patients with RA combined with arterial hypertension had significantly (by 10.9%) lower activity of the studied enzyme than those with no arterial hypertension. However, no significant relationship between paraoxonase activity and duration of the disease, obesity and smoking was revealed. Paraoxonase activity in RA patients was demonstrated to be dependent on lipid levels. The lowest paraoxonase activity was recorded in individuals with the highest levels of TC, LDLC and the lowest HDLC indices. Paraoxonase activity in RA patients is associated not only with atherosclerotic vascular damage (IMT, decreased FMDBA) but also with structural and functional heart status (systolic and diastolic functions, left ventricular myocardial hypertrophy). Decreased serum paraoxonase level is suggested to be the predictor of early development of cardiovascular complications in RA patients.